Routes, patterns, ideologies: navigating sacred sites in India - Dębicka-Borek, Ewa; Peres, Ofer (Ethno-Indology, 2025)
Hindu sacred geographies are shaped by interwoven webs of myth, ritual, and pilgrimage. Routes, Patterns, Ideologies: Navigating Sacred Sites in India brings together essays that offer in-depth explorations of Hindu sacred spaces, focusing on the relationships between sites as a crucial dimension of their theological and social significance. Drawing on textual analysis, visual studies, and ethnographic insights, the contributors to this volume illuminate the patterns and mechanisms that link sacred sites into dynamic networks, demonstrating how sacrality is continually negotiated through evolving cultural, political, and theological landscapes.
Keywords: Tīrtha; Māhātmya; Sthala-Purāna; Wallfahrt; Tempel; Hinduismus; Indien; Südasien